Differential Expression Profiles and Functional Prediction of circRNAs in Necrotizing Enterocolitis. (3rd November 2021) - Pan, Ya; Chen, Wenjuan; Yan, Xiangyun; Yu, Boshi; Yao, Shuwen; Chen, Xiaohui; Han, Shuping
Abstract : Circular RNAs (circRNAs), a novel type of noncoding RNAs, have been demonstrated to behave as microRNA (miRNA) sponges to exert their effects during pathological processes of diseases. However, the roles of circRNAs have not been explored in necrotizing enterocolitis (NEC). This study sought to identify differentially expressed circRNAs and predict their potential biological functions in NEC. circRNA expression profiles in terminal ileum from newborn rats with NEC and normal controls were explored using next-generation sequencing. In the NEC group, 53 circRNAs were significantly differentially expressed, including 9 upregulated and 44 downregulated. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were conducted, and circRNA-miRNA interaction networks were generated to predict the potential roles of circRNAs in NEC progression. Further investigation revealed that most circRNAs include miRNA binding sites and that some are implicated in NEC development. In conclusion, this study's findings demonstrate that differentially expressed circRNAs are involved in NEC development via their interactions with miRNAs, making them prospective targets for NEC diagnosis and treatment.